The Implications of Uncertainty in the Law of Criminal Causation for the One-Punch Homicide Offence in Western Australia - Jennifer Porter (Bond Law Review)
This article considers s 281 of the Criminal Code (WA), which was introduced in 2008 to create an offence ofunlawful assault causing death and to exclude the defence of accident (and the test of reasonableforeseeability) in those cases. The author argues that, given the ‘unfixed’ state of the common law of criminalcausation in Australia, triers of fact may still consider the reasonable foreseeability of consequences indeciding the primary question of causation. If triers of fact may still have regard to the reasonableforeseeability of consequences in deciding causation as a separate issue, then s 281 might not achieve what it isintended to achieve. An accused might be acquitted of a charge of unlawful assault causing death on the basisthat the death was not reasonably foreseeable even before the defence of accident arises. While this argumentremains open, s 281 may be a vehicle for further appellate consideration of the law of criminal causation andthe relationship of (legal) causation with accident in code jurisdictions.